Photocatalytic conversion of CO2 into solar fuels by surface modified TiO2 - Tng, Janus Yi Qian. (2013)
Industrialization results in a continuous increase in the emission of greenhouse gases into the atmosphere and affects the environment. Among these gases, carbon dioxide takes up a high percentage of 84%.